Síntese e caracterização do 5-TIO-D-glicose complexado com tecnécio, samário, gadolínio e hólmio para fins de diagnóstico e terapia - Marcelo Jose de Oliveira Maia (2007)
It is known that tumors and inflammations present a metabolic activity accentuated at the places where happen and they are disseminated. The demand of the organism for energy increases and the glucose presence is necessary for the cellular processes. Like this, a composed of glucose radiolabeled could serve as tracer to allow the generation of images, diagnoses and therapies of the cancerous processes. One of these drugs is the fluorodesoxiglicose, used in the technique Positron Emission Tomography. A obtain the 18F it is necessary an accelerator of particles and your half-life is of only 110 minutes. Such demand turns the clinical analyses for diagnosis and therapy with the very high cost. As proposal of an alternative road of the onerous use of the 18FDG, this work proposes the synthesis and characterization of four radiopharmaceuticals similar to the mentioned drug using the monosaccharide 5-thio-D-glucose. This sugar would be labeled then with the radionuclides: middle-stable technecium-99 (99mTc), samarium-153 (153Sm), gadolinium-159 (159Gd) and holmium-166 (166Ho); being obtained like this respective radiopharmaceuticals 99mTc-5-thio-D-glucose, 153Sm-5- thio-D-glucose, 159Gd-5-thio-D-glucose and 166Ho-5-thio-D-glucose. The drug radiolabeled 99mTc-5-thio-D-glucose doesn't request an accelerator of particles for your production. For the 99mTc a generator of the radionuclide is enough, as what it is produced and labeled by the Institute of Energy and Nuclear Researches, in the city of São Paulo, that supplies it for several clinics of nuclear medicine, besides in Belo Horizonte. The drugs 153Sm-5-thio-D-glucose, 159Gd-5-thio-D-glucose and 166Ho-5- thio-D-glucose already request for the production of the corresponding radionuclide a nuclear reactor, have seen that these radionuclides is produced by the more abundant and stable capture neutronic of the isotope. The success of these demarcations was confirmed by chromatography in thin layer with silica G, electronic spectrometry in the area of the ultraviolet-visible, molecular spectroscopy in the infrared and liquid chromatography of high efficiency. The perspectives of the use of the compositions 99mTc-5-thio-D-glucose, 153Sm-5-thio-D-glucose, 159Gd-5-thio-D-glucose and 166Ho-5-thio-D-glucose suggest the definition of new diagnosis protocols and therapy. Such progresses would mean an enormous economy for the area of the health, smaller expenses for the State as physical facilities and acquisition of foreign technology, besides they provide larger access of the treatments and diagnoses that request medical images for the less favored population. The present work means an alternative proposal to the production of new radiopharmaceuticals that they look for techniques economically viable for diagnoses and therapies of pathologies that today would be only possible through PET, inexistent in Belo Horizonte and in most of the great cities of Brazil and of the World due to prohibitive cost.